The The Role of Innovation Communication in the Development of Bali Aga - Sena Aji Prasetyo; Raphael Antonius Arnold Prawira; Ardo Ardhian (Communicare : Journal of Communication Studies, 2022)
As a priority of the Government of Indonesia's economic development, rural areas have been developing innovation which derived from the leading commodities of each region. In the process of developing innovation, rural areas also receive support from various parties in the form of training, facilities and infrastructure. The theory of communication related to innovation has been widely developed by researchers until the emergence of the concept of Innovation Communication. This concept is an interaction between stakeholders in an innovation process. Studies on Innovation Communication have not been widely carried out in rural areas. This study explores the role of innovation communication that can be a lesson for various parties in facing innovation challenges as well as plans for replicating good practices in rural areas. This study was conducted in the Bali Aga area, located in Buleleng Regency, Bali Province, using the constructivism paradigm. The researchers used a qualitative approach and collected data through in-depth interviews as well as field visit observations and report analysis. The results of the study indicate that there are challenges in changing the government structure of Buleleng Regency which have an impact on the commitment to innovation development that has been built by the local community. The researcher finds that the success of innovation development in rural areas is highly dependent on each role played by each stakeholder at the macro, meso, and micro levels. In addition, this study emphasizes the importance of the role of leaders as communication promoter who can encourage collaboration between parties.